2015
DOI: 10.1177/1937586715573745
|View full text |Cite
|
Sign up to set email alerts
|

Demonstrating the Effect of the Built Environment on Staff Health-Related Quality of Life in Ambulatory Care Environments

Abstract: This pilot study suggests that the more enhancements included in the interior features of a FQHC, the greater the returns to staff HRQoL. Findings also suggest that staff with a lower QWB appreciate enhancements more. Design strategies associated with improved staff well-being should be evaluated in terms of the amount of HRQoL they contribute.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…While much evidence acknowledges that the built environment affects staff well-being and effectiveness in delivering care, most studies have been conducted in hospitals and long-term care settings (Orfield, 2013;Perkins, Ball, Kemp, & Hollingsworth, 2013;Sikorska-Simmons, 2006;Wingler & Hector, 2015). Assessment of workers' perceptions of ALF environments is limited.…”
Section: Alfs and Staffingmentioning
confidence: 99%
See 1 more Smart Citation
“…While much evidence acknowledges that the built environment affects staff well-being and effectiveness in delivering care, most studies have been conducted in hospitals and long-term care settings (Orfield, 2013;Perkins, Ball, Kemp, & Hollingsworth, 2013;Sikorska-Simmons, 2006;Wingler & Hector, 2015). Assessment of workers' perceptions of ALF environments is limited.…”
Section: Alfs and Staffingmentioning
confidence: 99%
“…In the meantime, residents' thermal preferences should be given top priority in their living and activity spaces. Furthermore, it is necessary to limit the adjustment options of the thermostats to prevent unnecessary confusion (Wingler & Hector, 2015).…”
Section: Factor 4: Thermal Comfortmentioning
confidence: 99%
“…First, the mapping workflow creates a comprehensive journey map of a patient to identify bottlenecks and other inefficiencies in the ED clinical course. Winger and Hector (2015) previously studied the effect of the ED built environment on ED staff. Through surveys, they found that the layout of the care space affected staff productivity.…”
Section: Discussionmentioning
confidence: 99%
“…Larsen et al [80] designed a tool to evaluate the holistic IEQ performance using 16 parameters without considering occupants. The 'impact' focused on the inter-relationships between IEQ factors and/or the effects of IEQ factors on building occupants, and researchers have been studying this area since 2010 [81][82][83]. Another noteworthy new keyword after 2016 is 'occupant behaviour', which indicates the increasing research interest in the effect of occupants' behaviours on IEQ [84][85][86].…”
Section: Keyword Changes Analysismentioning
confidence: 99%